2017
DOI: 10.1007/s12574-017-0347-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased apical rotation in patients with severe aortic stenosis assessed by three-dimensional speckle tracking imaging

Abstract: In severe AS patients, impaired GLS existed although LVEF was preserved. However, LV rotation was increased in patients with severe AS probably to maintain the LV stroke volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Changes in LV rotation have been observed at the early phase of many cardiac diseases, and they even precede changes in longitudinal and circumferential strain (18). Aging, hypertension, hypertrophic cardiomyopathy and aortic stenosis are all characterized by increased apical rotation and delayed rotation with longer untwisting (18)(19)(20)(21)(22). Anthracycline treatment has induced a decline in both apical and basal rotation along with an overall twist becoming declined and delayed (23).…”
Section: Changes In Apical Strain In the Follow-up According To Brementioning
confidence: 99%
“…Changes in LV rotation have been observed at the early phase of many cardiac diseases, and they even precede changes in longitudinal and circumferential strain (18). Aging, hypertension, hypertrophic cardiomyopathy and aortic stenosis are all characterized by increased apical rotation and delayed rotation with longer untwisting (18)(19)(20)(21)(22). Anthracycline treatment has induced a decline in both apical and basal rotation along with an overall twist becoming declined and delayed (23).…”
Section: Changes In Apical Strain In the Follow-up According To Brementioning
confidence: 99%
“…Several studies have shown that rotation and twist is higher in patients with more severe AS 19,20,30 . Using 2D STE, Holmes et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that rotation and twist is higher in patients with more severe AS. 19,20,30 Using 2D STE, Holmes et al found increased apical rotation to be associated with poor survival in severe AS, suggesting apical rotation as a compensatory mechanism to preserve cardiac output in severe LV outflow obstruction. 19 In the present study, only basal rotation was higher in the severe AS group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations